Analisis Rasa Nasionalisme Masyarakat Aceh Pasca Konflik Gerakan Aceh Merdeka - Rahma Syakira Ayu; Rizka Luluatul Hasanah; Ronaldo Febryan; Shalwa Azahra; Ardli Johan Kusuma (CV. ITTC INDONESIA, 2024)
This research aims to analyze the sense of nationalism of the Acehnese people after the conflict with the Free Aceh Movement (GAM), as well as finding out how the feeling of